Perfectionism and Self-esteem in Argentine University Students - Helguera, Gisela Paola; Oros, Laura Beatriz (Pensando Psicología, 2018)
Objective: To explore the extent to which perfectionism and self-esteem are related to Argentine university students.Method: Three hundred and forty-one subjects answered the Almost Perfect Scale-Revised and the Rosenberg Self-Esteem Scale.Results: The results showed a significant, robust, negative relationship between self-esteem and perfectionist discrepancy (r = -0,53; p < 0,001), and a weak but significant relationship between selfesteem and high standards (r = 0,19; p
Keywords: APS-R; self-esteem; Argentine university students; perfectionism